Elmer Kelton : essays and memories - Lee, James Ward; Alter, Judy, 1938- (TCU Press, 2011)
When Elmer Kelton died in the fall of 2009, the literary world lost a consummate writer, a man the New York Times called a "novelist who brought the sensibility of the old-style western to bear on a modern Texas landscape of oil fields and financially troubled ranches." Kelton was also a modest, kind man, always willing to advise a struggling writer or write a blurb for a first time published author, or assign publishing rights to his six masterpieces to a small university press.?TCU Press owes a great debt of gratitude to Kelton, and this volume, Elmer Kelton: Memories and Essays, attempts to explore just what it is that made Kelton its leading author.?Editors Judy Alter and James Ward Lee gathered together a group of Kelton aficionados who had either published or taught or sold his books, or were simply friends. In several meetings, they divided up the main themes of Kelton?s writing: Alter provides the overview of Kelton?s career; Felton Cochran, longtime owner of Cactus Books in San Angelo, describes how the friendship between bookstore owner and author grew over the years; Ricky Burk, pastor of the church from which Kelton was buried, talks about the man?s influence in his community; Kelton?s son, Steve, explains how Kelton?s career as journalist permeated his novels; Ruth McAdams, who has taught Kelton for years, explores how he deals with the themes of endurance and change; Joyce Roach delicately covers how race and ethnicity figure in Kelton?s plots and the development of his unforgettable characters;?Lee gives readers his inimitable take on the Hewey Calloway Trilogy?The Good Old Boys, The Smiling Country, and Six Bits a Day; and Bob J. Frye takes a wry look at Kelton?s use of humor throughout his career. The book also contains Kelton?s own view of the history of the Western novel, a response to revisionist criticism. And finally Cochran provides us a list of most, not all, of Elmer Kelton?s extraordinary body of work.